“HIV is Only One Part of Me”: HIV and Its Effect on Other Identities - Lisa M. Baumgartner; Keegan N. David (Adult Education Research Conference, 2010)
The purpose of this study was to investigate the effect of the HIV identity on other identities. The spiritual and advocate identities increased in salience whereas work and sexual identities decreased. Younger participants fretted about physical appearance. Older participants focused on health. There are implications for adult educators.